Analysis of Internal Control of Raw Material Supplies at Ibu Elta's Bakery Using the FIFO Method in Bandung Ayu Village, Pino Raya Subdistrict, South Bengkulu Regency - Ulva, Marya; Kresnawati , Kresnawati; Harwini , Dewi (Universitas Dehasen Bengkulu, 2025)
This research aims to analyze the internal control of raw material inventory at Usaha Roti Ibu Elta by applying the FIFO (First In, First Out) method. Internal control plays a crucial role in ensuring the availability of raw materials in accordance with production requirements, preventing material deterioration, and maintaining efficiency in their utilization. The study emphasizes the importance of implementing an effective inventory control system to support smooth production activities and optimize operational performance. This research employed a descriptive quantitative method, with data obtained through direct observation, in-depth interviews, and documentation conducted during the period of May to August 2025. The results revealed that the internal control system for raw material inventory at Usaha Roti Ibu Elta has generally been functioning quite well, although it is still managed manually. The consistent implementation of the FIFO method has proven effective in maintaining the quality of raw materials, reducing the risk of stock accumulation and product spoilage, and enhancing overall production efficiency. Nevertheless, the manual recording system still poses potential risks of errors and data inaccuracies. Therefore, it is strongly recommended to adopt a digital-based inventory recording system to improve accuracy, efficiency, and the overall reliability of internal control processes in managing raw materials.